Fuzzy modeling of the risk of cacao moniliasis occurrence in Bahia state, Brazil - Almeida, Samira L. H. de [UNESP]; Silva, Samuel de A.; Lima, Juliao S. de S.; Rosas, Jorge T. F.; Capelini, Vinicius A. (Univ Federal Campina Grande, 2020)
This work aimed to determine potential areas for the establishment of cocoa moniliasis in Bahia state, Brazil, by means of fuzzy logic, based on historical datasets of temperature and air relative humidity, available for 519 measurement points distributed throughout the state of Bahia. The data were initially submitted to a descriptive statistical analysis. The spatial variability was determined through geostatistical analysis, followed by interpolation to map the spatial-temporal structure dependence of the phenomenon. Simulations of continuous pixel-to-pixel classification of variables were performed using fuzzy mapping to model the climatic risk of disease establishment. The exponential fuzzy model was applied to temperature data, while the linear model was used for air relative humidity data. The potential areas were defined for each month, using data of temperature and air relative humidity. The fuzzy models used allowed for modeling of the climatic risk of cocoa moniliasis establishment. A large area of the state is at high risk of disease, thus requiring mitigating measures to avoid the pathogen's introduction and dissemination.
Keywords: Moniliophthora roreri; Theobroma cacao; climate change; geostatistics; precision phytopathology